An autosomal recessive syndrome of cleft palate, cardiac defect, genital anomalies, and ectrodactyly (CCGE). Issue 1 (January 1995) - Giannotti, A; Digilio, M C; Mingarelli, R; Dallapiccola, B
Abstract : We report a brother and sister affected by a constellation of malformations, including cleft palate, cardiac defect, genital anomalies, and ectrodactyly (CCGE). A similar association has been reported previously by Richieri-Costa and Orquizas in a male patient born to consanguineous parents. An autosomal recessive pattern of inheritance is proposed for this syndrome.